Biomass‐derived furanic polycarbonates: Mild synthesis and control of the glass transition temperature. Issue 17 (29th July 2019) - Choi, Eun Ho; Lee, Juhyen; Son, Seung Uk; Song, Changsik
ABSTRACT: Bis(hydroxymethyl)furan (BHMF) is a promising biomass‐derived polymer platform, but it is incompatible with traditional methods used for synthesizing polycarbonates (PCs) owing to its thermal instability. In this study, BHMF‐based furanic (FR) PCs were prepared successfully at a relatively low temperature through the mediation of carbonyldiimidazole. The low T g of aliphatic FR‐PCs was controlled elaborately, exploiting the reactivity of furan in the Diels–Alder reactions and the molecular rigidity of the resulting oxabicycles. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1796–1800 Abstract : The synthesis of sustainable bis(hydroxymethyl)furan‐derived furanic polycarbonate (FR‐PC) is reported. The T g of FR‐PC was controlled successfully with the Diels–Alder reaction which increases the rotational barrier of the polymer chain.